2020
DOI: 10.1042/bsr20200084
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ultrasound-guided supraclavicular and costoclavicular brachial plexus block using a modified double-injection technique: a randomized non-inferiority trial

Abstract: Ultrasound-guided costoclavicular block (CC-approach) is a recently described brachial plexus block (BPB) and an alternative approach to the supraclavicular approach (SC-approach). The relevant sonoanatomy is analogous in terms of the brachial plexus and its adjacent artery for both approaches. In the present study, we hypothesized that the two approaches will result in similar block dynamics when used the modified double-injection (MDI) technique. One hundred and twelve patients were randomly allocated to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…A total of 53 articles were included in this systematic review: 38 hand studies and 15 shoulder studies ( Table S1 , available on the Journal’ s website at www.jhsgo.org ). 18 , 19 , 20 , 21 , 23 , 24 , 25 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 These 53 articles comprised 73 discrete, surgery-block combination study groups (54 hand and 19 shoulder groups) and 6,579 total subjects (2,875 hand and 3,704 shoulder subjects; Table 1 ). The large majority of studies in both groups were RCTs (94.4% hand and 78.9% shoulder RCTs); most were single-blind.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 53 articles were included in this systematic review: 38 hand studies and 15 shoulder studies ( Table S1 , available on the Journal’ s website at www.jhsgo.org ). 18 , 19 , 20 , 21 , 23 , 24 , 25 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 These 53 articles comprised 73 discrete, surgery-block combination study groups (54 hand and 19 shoulder groups) and 6,579 total subjects (2,875 hand and 3,704 shoulder subjects; Table 1 ). The large majority of studies in both groups were RCTs (94.4% hand and 78.9% shoulder RCTs); most were single-blind.…”
Section: Resultsmentioning
confidence: 99%
“…Luo et al were the first to compare the efficiency of ultrasound-guided SC-BPB and CC-BPB in similar block dynamics (13) and found similarity between the two. However, they applied a novel modified double-injection technique, which may have affected the results.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date there are very few studies comparing the efficiencies of ultrasound-guided CC-BPB and SC-BPB in regional blockade in upper extremity surgery. The first of these was a randomized non-inferiority trial conducted by Luo et al (13) using a modified double-injection technique which found ultrasound-guided CC-BPB and SC-BPB could result in similar block dynamics. As this technique improved the efficiencies of both approaches, a comparative study of conventional ultrasound-guided CC-BPB and SC-BPB is needed to determine the efficiencies, advantages, and disadvantages of the two methods.…”
Section: Original Articlementioning
confidence: 99%
“…In obese patients, the costoclavicular space is situated within a layer of fat, the pectoralis major, and the subclavian muscle, which can impede proper needle visualization. These patients are at a higher risk of multiple needle attempts, puncturing the cephalic, axillary veins, and even the acromial artery [ 81 ]. To overcome these challenges, some researchers suggest approaching the subclavicular region from medial to lateral to enhance needle visualization by avoiding interference from the coracoid process.…”
Section: Limitations Of Ccbmentioning
confidence: 99%
“…In the case of CCB, the neurovascular structures within the costoclavicular space are closely situated and immobile. However, during the nerve block procedure, there is a risk of inadvertently puncturing blood vessels due to the unclear visualization of tissue vessels or needle tips [ 81 ]. This can result in bleeding and subsequent compression of the brachial plexus.…”
Section: Limitations Of Ccbmentioning
confidence: 99%